Transculturated elements in «Ángel de Ocongate» («Angel of Ocongate») by Edgardo Rivera Martínez - Huaman Malasquez, Luis Alejandro Juan (2023)
In spite of its reduced length, «Ángel de Ocongate» (1982), by Edgardo Rivera Martínez, is a singular story: it shows Andean elements that are in a crosstranscultural. For this reason, in order to draw new conclusions, it is necessary to carry out an analytical revision of the text using multiple tools that externalize the conflicts surrounding these elements. Therefore, the orientation of the present work will cover those objectives. After a deep literary analysis, we will apply the concepts of yanantin, tinkuy and wakcha around the data obtained to evidence the roots that give shape to the problematic of identity suffered by the protagonist.